"We Don't Need Money, We Need to be Together": Forced Transnationality in Deportation's Afterlives. Issue 1 (2nd January 2017) - Ybarra, Megan; Peña, Isaura L.
ABSTRACT: As US deportations and repatriations climbed to unprecedented levels, half of Mexican immigrants deported have at least one family member who is a US citizen, and one in five have at least one child who is a US citizen. This paper applies the analytic of forced transnationality, extending its scope beyond one person's deportation to reveal cascading effects of travel and trauma for families remaking lives across the US-Mexico border. To do so, our research draws on interviews with mixed-status families, where transnational children have legal permission to reside in the US (including citizenship) and live with caregivers (like parents) who do not. In the wake of the rupture of prolonged detention and deportation, families seek to suture themselves as a collective social subject that is reshaped by forced transnationality.